1995
DOI: 10.1111/j.1440-1681.1995.tb01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Voluntary Apnoea, Exposure to Cold and Face Immersion in Water to Diving Bradycardia in Humans

Abstract: 1. Diving or face immersion bradycardia is a well recognized but incompletely understood reflux which occurs in man and other mammals. 2. In order to investigate the contributions made by voluntary apnoea, face immersion in water and cold exposure, 18 normal subjects were exposed to these challenges separately and in various combination. 3. Tested individually, cold and apnoea caused significant reductions in heart beat (P < 0.01 and 0.002, respectively). Face immersion in thermoneutral water had no effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 6 publications
(5 reference statements)
2
11
0
1
Order By: Relevance
“…The heart rate reduction and selective vasoconstriction elicited by apnoea without immersion were augmented by immersion of the face in cold water, as reported previously (Kawakami et al 1967;Hurwitz and Furedy 1986;Marsh et al 1995;Andersson and Schagatay 1998a). However, forearm immersion did not aect the cardiovascular responses during apnoea as it did during eupnoea (i.e.…”
Section: Discussionmentioning
confidence: 50%
“…The heart rate reduction and selective vasoconstriction elicited by apnoea without immersion were augmented by immersion of the face in cold water, as reported previously (Kawakami et al 1967;Hurwitz and Furedy 1986;Marsh et al 1995;Andersson and Schagatay 1998a). However, forearm immersion did not aect the cardiovascular responses during apnoea as it did during eupnoea (i.e.…”
Section: Discussionmentioning
confidence: 50%
“…In this study by Schagatay and Holm (1996), subjects' faces were immersed in water at a temperature of 10 and 20 1C while the ambient air temperature was 30 1C; the results showed that a water temperature of 20 1C also augments diving bradycardia at warmer air temperatures. Occurring together, apnea, face immersion in water, and cold exposure have a synergistic effect on diving bradycardia, which is greater than the sum of each individual response (Marsh et al, 1995).…”
Section: Face Immersionmentioning
confidence: 96%
“…First, swimming combines exertion, voluntary apnea, possible cold-water exposure, and face immersion, resulting in increased sympathetic and parasympathetic activity through activation of the "dive reflex." 24,25 This concomitant activation of both the sympathetic and parasympathetic autonomic system may explain why swimming seems to precipitate premature ventricular contractions. 26 Second, cold-water face immersion has been demonstrated to lengthen QT intervals in normal subjects and occasionally induce T-wave alternans.…”
Section: Discussionmentioning
confidence: 99%